2009
DOI: 10.1097/rli.0b013e31819e9362
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropy of Callosal Motor Fibers in Combination With Transcranial Magnetic Stimulation in the Course of Motor Development

Abstract: The maturation of callosal motor fiber connectivity seems to reflect the degree of interhemispheric inhibition between the motor cortices with anisotropy of callosal motor fibers being a potential marker for motor development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
36
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 35 publications
4
36
0
Order By: Relevance
“…Similarly, a positive relationship between interhemispheric inhibition (assessed by iSP area and duration) and callosal microstructure across development (range: ~7–26 yrs. ; Koerte et al, 2009) has been shown. However, further analysis of Koerte and colleagues’ dataset is warranted; it is clear that the observed relationship is strongly driven by the child group in their study (mean age: 8.4 yrs).…”
Section: Introductionmentioning
confidence: 92%
“…Similarly, a positive relationship between interhemispheric inhibition (assessed by iSP area and duration) and callosal microstructure across development (range: ~7–26 yrs. ; Koerte et al, 2009) has been shown. However, further analysis of Koerte and colleagues’ dataset is warranted; it is clear that the observed relationship is strongly driven by the child group in their study (mean age: 8.4 yrs).…”
Section: Introductionmentioning
confidence: 92%
“…Poorer motor performance is reported in individuals with compromised inhibitory capacity such as children with premyelinated interhemispheric fibers [11] or patients with multiple sclerosis [12]. On the other hand, IHI is also reduced in musicians (experts in manual motor control) compared to non-musicians [5, 13], and studies demonstrate that IHI is decreased with a concomitant improvement in bimanual motor control following brief training interventions [6,14].…”
Section: Introductionmentioning
confidence: 99%
“…6,7 Physiologic myelination is known to expand well into early adulthood in conjunction with cognitive, behavioral, emotional, and motor development. [8][9][10] Any pathology interfering with this process of myelination is likely to affect white matter integrity as has been shown in hypoxic-ischemic encephalopathy, former premature in-fants, and normal-pressure hydrocephalus. 11 The onset of childhood MS occurs within this vulnerable period of central nervous system maturation.…”
mentioning
confidence: 99%